DNA Virome: Sequencing and Data Analysis of Viral Metagenome of Poultry Suffering from Respiratory Diseases - Sajnani, Manisha R; Sudarsanam, D; Jhakeshara, Subhash; Joshhi, Chaitanya J; Bhatt, Vaibhav D (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Respiratory diseases are the most common causes of death in a poultry flock. Knowledge of the avian respiratory system is essential for developing a health monitoring plan for a poultry flock, recognizing problems that may occur, and taking action to correct them. Recently, respiratory diseases in commercial broiler chicken flocks have increased in India and no significant cause has been identified till date. Viral populations are predominant in respiratory tract infections and they cause severe economic loss through decreased productivity. We performed shotgun sequencing approach to understand viruses associated with or causing respiratory infections (RI) in broilers. We report high quality sequencing reads, de novo assembled sequences, taxonomical as well as functional classifications of virome of the infected broiler birds.